Pengaruh perceived organisational support dan work-life balance terhadap organisational citizenship behaviour - Bekti, Amini Iin Tri; Fatoni, Fandi (Jurnal Ilmu Manajemen, 2025)
This research aims to determine and analyse the influence of perceptions of perceived organisational support and work-life balance on organisational citizenship behaviour. This research is causal research using a quantitative approach, with a population of 132 employees and a sample of 99 employees. The statistical analysis method in this research is Structural Equation Modeling - Partial Least Square (SEM-PLS) supported by SmartPLS 4.1.0.0 software. The results of this study indicate that there is a positive and significant influence of perceived organisational support on altruism, there is no significant influence of perceived organisational support on conscientiousness, there is no significant influence of perceived organisational support on sportsmanship, there is a positive and significant influence of perceived organisational support on courtesy, there is a positive and significant influence of perceived organisational support on civic virtue, there is a positive and significant influence of work-life balance on altruism, there is a positive and significant influence of work-life balance on conscientiousness, there is a positive and significant influence of work-life balance on sportsmanship, there is a positive and significant influence of work-life balance on courtesy, there is a positive and significant influence of work-life balance on civic virtue. Companies that want to improve organisational citizenship behaviour must pay more attention to perceptions of perceived organisational support and work-life balance that influence each dimension.